Volatility reversion and correlation structure of returns in major international stock markets - Theodossiou, Panayiotis; Kahya, Emel; Koutmos, Gregory; Christofi, Antreas (My University, 1997)
This paper investigates the stochastic behavior of weekly stock market returns in the U.S., Japan, and the U.K. during the period 1984 to 1994. The analysis is carried out using an augmented version of Bollerslev’s [7] multivariate GARCH model with structural dummies to test for differences in the mean, volatility, and covariance structure of returns during the pre- and post-October 1987 crash periods. In addition, the paper explores the issue of the volatility reversion and time-varying behavior of correlation structure of returns in these markets. Mean-spillovers exist from the U.S. and Japan to the U.K. The magnitude of these spillovers is, however, low. Volatility spillovers exist from the U.S. and, to a lesser extent, from Japan to the U.K. Mean returns in all three markets and volatility in Japan and the U.K. are the same during the two periods, while volatility in the U.S. is lower during the post-crash period. With the exception of the correlation of returns between Japan and the U.K., which has doubled since the October 1987 crash, the remaining correlations are statistically similar during the two periods. Simulations performed indicate that volatility is reverting in the sense that, when it departs from its long-run equilibrium level, it tends to revert back to that level